2022
DOI: 10.1021/acs.orglett.2c03736
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Driven Synthesis of Aryl Xanthates and Aryl Dithiocarbamates via an Electron Donor–Acceptor Complex

Abstract: Herein, we report a facile, efficient, and practical protocol that enables the preparation of aryl xanthates and aryl dithiocarbamates from functionalized dibenzothiophenium salts via a photoactivated electron donor–acceptor complex. This mild, metal-free method is operationally simple and has a broad substrate scope and potential utility for late-stage functionalization of natural products and pharmaceuticals. Finally, this method also has redefined the substrate scope and reaction pathway for the Leuckart th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…In our recent study, we observed that S-arylation of potassium O -ethyl xanthate with aryl halides through an EDA-based visible light-driven process did not lead to the formation of S -aryl O -alkylxanthates but rather to aryl ethyl sulfides, arising from the reaction of the initially formed S -aryl O -ethylxanthates with an excess of potassium O -ethyl xanthate . Similarly, other groups reported on the formation of alkyl aryl thioethers as the side or only products in the arylation of xanthates through mechanistically distinct reactions . Despite its potential synthetic utility, the conversion of xanthates to thioethers is mostly regarded as an undesired side process and remains a rather underexplored transformation with few precedents limited to nonfunctionalized primary alcohols. , As a continuation of our recent work on the arylation of O -alkyl xanthates with diaryliodonium salts to obtain S -aryl xanthates, herein, we report on the related cascade transformation of primary and secondary alcohols into the corresponding alkyl aryl thioethers using CS 2 as a sulfur source and diaryliodonium salts as arylating agents.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In our recent study, we observed that S-arylation of potassium O -ethyl xanthate with aryl halides through an EDA-based visible light-driven process did not lead to the formation of S -aryl O -alkylxanthates but rather to aryl ethyl sulfides, arising from the reaction of the initially formed S -aryl O -ethylxanthates with an excess of potassium O -ethyl xanthate . Similarly, other groups reported on the formation of alkyl aryl thioethers as the side or only products in the arylation of xanthates through mechanistically distinct reactions . Despite its potential synthetic utility, the conversion of xanthates to thioethers is mostly regarded as an undesired side process and remains a rather underexplored transformation with few precedents limited to nonfunctionalized primary alcohols. , As a continuation of our recent work on the arylation of O -alkyl xanthates with diaryliodonium salts to obtain S -aryl xanthates, herein, we report on the related cascade transformation of primary and secondary alcohols into the corresponding alkyl aryl thioethers using CS 2 as a sulfur source and diaryliodonium salts as arylating agents.…”
Section: Resultsmentioning
confidence: 81%
“…Similarly, other groups reported on the formation of alkyl aryl thioethers as the side or only products in the arylation of xanthates through mechanistically distinct reactions . Despite its potential synthetic utility, the conversion of xanthates to thioethers is mostly regarded as an undesired side process and remains a rather underexplored transformation with few precedents limited to nonfunctionalized primary alcohols. , As a continuation of our recent work on the arylation of O -alkyl xanthates with diaryliodonium salts to obtain S -aryl xanthates, herein, we report on the related cascade transformation of primary and secondary alcohols into the corresponding alkyl aryl thioethers using CS 2 as a sulfur source and diaryliodonium salts as arylating agents. From a synthetic perspective, this operationally simple one-pot protocol affords a shorter synthetic route to alkyl aryl thioethers without a need for the use or preparation of thiols.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to feedstock derived thianthrenium salts, derivatives of the lipid lowering agent gemfibrozil, and the NSAID indomethacin formed the corresponding sulfones in moderate yields (42 and 20%, respectively). Z. Wang, Q. Wang and co-workers exploted an analogous EDA formation event between thianthrenium salts ( 76.9 ) and xanthates ( 76.10 ) or dithiocarbamates ( 76.11 ) to produce the corresponding aryl derivatives ( 76.12 – 13 , Scheme D) . Simple 390 nm LED irradiation in acetonitrile was sufficient to afford the corresponding C–S coupled products.…”
Section: Late-stage Aromatic C(sp2)–h Functionalizationmentioning
confidence: 99%
“… Exploitation of aryl sulfonium salts in EDA complexes with dithioate donors; application in the synthesis of aryl xanthates and aryl dithiocarbamates [28] …”
Section: Aryl Radical Generationmentioning
confidence: 99%